Furfuryl alcohol / acrylamide composite modified wood and preparation method thereof

Through the use of furfuryl alcohol/acrylamide composite modifier, the problem of insufficient toughness and dimensional stability of furfuryl alcohol modified wood is solved, the coefficient of moisture swelling and impact strength are improved, and the performance of wood is significantly improved.

CN119260875APending Publication Date: 2025-01-07NORTHEAST FORESTRY UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411608516.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing furfuryl alcohol-modified woods have problems of reduced toughness and low dimensional stability.

Method used

Using furfuryl alcohol/acrylamide composite modifier, oligomerization reactions are carried out by furfuryl alcohol, maleic anhydride, borax and acrylamide under acidic conditions to form furfuryl alcohol oligomers, and impregnate and vacuum pressurize with wood, and finally heat it After curing, a three-dimensional network structure is formed, which reduces the density of the resin and improves the anti-swelling coefficient and impact strength of the wood.

Benefits of technology

It significantly improves the wet swelling coefficient and impact strength of the wood, improves brittleness, and does not affect the original excellent properties of the wood, and enhances dimensional stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260875A_ABST
    Figure CN119260875A_ABST
Patent Text Reader

Abstract

The invention discloses furfuryl alcohol / acrylamide composite modified wood and a preparation method thereof, and belongs to the field of modified wood. The invention aims to solve the problems that the toughness is reduced and the dimensional stability is relatively low after wood is modified by furfuryl alcohol at present. The furfuryl alcohol / acrylamide composite modified wood is obtained after wood is modified by utilizing a furfuryl alcohol / acrylamide modifier; the furfuryl alcohol / acrylamide modifier is prepared from furfuryl alcohol, maleic anhydride, borax, acrylamide and a solvent. The method comprises the following steps: 1, weighing; 2, preparing a furfuryl alcohol oligomer; 3, uniformly mixing the furfuryl alcohol oligomer with the weighed acrylamide; fourthly, the wood is soaked in a furfuryl alcohol / acrylamide modifier, and then vacuum and pressurization treatment is conducted; and 5, heating, curing and drying. The invention is used for furfuryl alcohol / acrylamide composite modified wood and preparation thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of modified wood. Background Art

[0002] Artificial fast-growing forests have great application potential in the fields of construction, furniture and decoration due to their advantages of short growth cycle, fast growth rate and high yield per unit area. As these trees grow quickly, they usually have problems such as soft material, low density and easy deformation, which limits their application in the field of high value-added products. Modification of artificial fast-growing forest wood by physical or chemical means can improve its basic physical properties or give it functional characteristics.

[0003] At present, common chemical modification methods include acetylation, nitrogen hydroxymethyl resin modification, urea-formaldehyde resin treatment, furfuryl alcohol resin treatment, organic monomer treatment, and sol-gel treatment. Depending on the different mechanisms of action between the modifier and wood, chemical modification of wood can be carried out in the following different ways: grafting reaction with cell walls, filling cell walls, and filling cell cavities. Different modification methods can also modify wood in one or more ways to achieve the best effect.

[0004] Furfuryl alcohol is a polar organic monomer derived from agricultural and forestry waste (such as bagasse, straw and corn cobs, etc.), which is more environmentally friendly than other modifiers. Furfuryl alcohol monomer undergoes dehydration condensation reaction to form conjugated short chains, which continue to cross-link to form highly polymerized furfuryl alcohol resin. The molecular weight of furfuryl alcohol monomer is 98, which can easily penetrate into the wood cell wall, and then polymerize in situ to form resin to fill in the wood cell wall, so as to achieve the densification of loose wood. Furfuryl alcohol modified wood technology has been industrialized. Since furfuryl alcohol resin hardly reacts chemically with wood components, it can only block the water transport channel by physical filling, and the method of improving dimensional stability is relatively single. In addition, the three-dimensional network molecular structure formed after the curing of furfuryl alcohol resin is too dense, which limits the movement of molecules, making it difficult for the molecular chain to slip when subjected to external force, and the glass transition temperature of furfuryl alcohol resin is between 70℃ and 130℃. At room temperature, furfuryl alcohol resin is in a glassy state, so furfuryl alcohol modified wood often has the problem of increased brittleness. Summary of the invention

[0005] The invention aims to solve the problems of reduced toughness and low dimensional stability of existing furfuryl alcohol-modified wood, and further provides furfuryl alcohol / acrylamide composite-modified wood and a preparation method thereof.

[0006] A furfuryl alcohol / acrylamide composite modified wood, which is obtained by modifying the wood with furfuryl alcohol / acrylamide modifier;

[0007] The furfuryl alcohol / acrylamide modifier is prepared from furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent.

[0008] A method for preparing furfuryl alcohol / acrylamide composite modified wood is carried out according to the following steps:

[0009] 1. Weigh furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent;

[0010] 2. adding the weighed furfuryl alcohol, maleic anhydride and borax into a solvent to form an acidic solution, and then carrying out an oligomerization reaction under heating conditions to obtain furfuryl alcohol oligomers;

[0011] 3. Evenly mixing the furfuryl alcohol oligomer and the weighed acrylamide to obtain a furfuryl alcohol / acrylamide modifier;

[0012] Fourth, the wood is impregnated in the furfuryl alcohol / acrylamide modifier, and then vacuum and pressure treated to obtain the impregnated wood;

[0013] Fifth, the impregnated wood is heated and cured, and finally dried to obtain furfuryl alcohol / acrylamide composite-modified wood.

[0014] The beneficial effects of the present invention are:

[0015] 1. The present invention heats the furfuryl alcohol monomers under acidic conditions to cause a dehydration condensation reaction between the furfuryl alcohol monomers to form short chains. In the subsequent heating and curing stage, the short chains can directly continue to react to form a three-dimensional network structure to generate furfuryl alcohol resin, fill the cell pores, and improve the curing efficiency;

[0016] 2. The carbon-carbon double bonds in the acrylamide of the present invention can participate in the conjugation reaction between the short chains of furfuryl alcohol, reduce the density of the three-dimensional network structure of the furfuryl alcohol resin, and allow the molecular chains to have more room for movement;

[0017] 3. After adding acrylamide, the present invention will not significantly affect the original excellent properties of furfuryl alcohol wood;

[0018] 4. After adding acrylamide in the present invention, the anti-swelling coefficient of wood reaches 36.28%, and the dimensional stability is better than that of furfuryl alcohol wood;

[0019] 5. After acrylamide is added to the present invention, the impact strength of the wood is increased by 44.43% compared with furfuryl alcohol wood, and the brittleness is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart for preparing furfuryl alcohol / acrylamide composite modified wood;

[0021] Figure 2This is a comparison chart of the anti-expansion coefficients of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment;

[0022] Figure 3 This is a density comparison diagram of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment;

[0023] Figure 4 This is a comparison chart of the impact strength of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment;

[0024] Figure 5 This is a comparison chart of the bending strength of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment;

[0025] Figure 6 This is a comparison chart of the bending modulus of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment;

[0026] Figure 7 are scanning electron microscope images, a) is untreated wood, b) is furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1;

[0027] Figure 8 This is a comparison chart of the weight gain rates of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment. DETAILED DESCRIPTION

[0028] Specific implementation method 1: This implementation method is a furfuryl alcohol / acrylamide composite modified wood, which is obtained by modifying wood with furfuryl alcohol / acrylamide modifier;

[0029] The furfuryl alcohol / acrylamide modifier is prepared from furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent.

[0030] The beneficial effects of this embodiment are:

[0031] 1. In this embodiment, the furfuryl alcohol monomers are heated under acidic conditions to cause a dehydration condensation reaction between the furfuryl alcohol monomers to form short chains. In the subsequent heating and curing stage, the short chains can directly continue to react to form a three-dimensional network structure to generate furfuryl alcohol resin, fill the cell pores, and improve the curing efficiency;

[0032] 2. The carbon-carbon double bonds in acrylamide in this embodiment can participate in the conjugation reaction between the short chains of furfuryl alcohol, reduce the density of the three-dimensional network structure of the furfuryl alcohol resin, and allow the molecular chains to have more room for movement;

[0033] 3. After adding acrylamide in this embodiment, the original excellent properties of furfuryl alcohol wood will not be significantly affected;

[0034] 4. After adding acrylamide in this embodiment, the anti-swelling coefficient of wood reaches 36.28%, and the dimensional stability is better than that of furfuryl alcohol wood;

[0035] 5. After acrylamide is added in this embodiment, the impact strength of the wood is increased by 44.43% compared with the furfuryl alcohol wood, and the brittleness is significantly improved.

[0036] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the furfuryl alcohol / acrylamide modifier is prepared by 10 to 60 parts of furfuryl alcohol, 1 to 2 parts of maleic anhydride, 2 to 4 parts of borax, 1.81 to 10.86 parts of acrylamide and 23.14 to 85.19 parts of solvent by mass. The rest is the same as the specific embodiment 1.

[0037] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the solvent is water or alcohol. The other aspects are the same as specific implementation method 1 or 2.

[0038] Specific implementation method four, combined with Figure 1 Specific description: The preparation method of furfuryl alcohol / acrylamide composite modified wood in this embodiment is carried out according to the following steps:

[0039] 1. Weigh furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent;

[0040] 2. adding the weighed furfuryl alcohol, maleic anhydride and borax into a solvent to form an acidic solution, and then carrying out an oligomerization reaction under heating conditions to obtain furfuryl alcohol oligomers;

[0041] 3. Evenly mixing the furfuryl alcohol oligomer and the weighed acrylamide to obtain a furfuryl alcohol / acrylamide modifier;

[0042] Fourth, the wood is impregnated in the furfuryl alcohol / acrylamide modifier, and then vacuum and pressure treated to obtain the impregnated wood;

[0043] Fifth, the impregnated wood is heated and cured, and finally dried to obtain furfuryl alcohol / acrylamide composite-modified wood.

[0044] Specific embodiment 5: This embodiment differs from specific embodiment 4 in that: in step 1, 10 to 60 parts of furfuryl alcohol, 1 to 2 parts of maleic anhydride, 2 to 4 parts of borax, 1.81 to 10.86 parts of acrylamide and 23.14 to 85.19 parts of solvent are weighed by mass. The rest is the same as specific embodiment 4.

[0045] Specific implementation method 6: This implementation method is different from specific implementation method 4 or 5 in that the solvent in step 1 is water or alcohol. The rest is the same as specific implementation method 4 or 5.

[0046] Specific embodiment 7: This embodiment is different from any one of specific embodiments 4 to 6 in that: in step 2, the oligomerization reaction is carried out at a temperature of 30° C. to 60° C. for 0.5 h to 1 h. The rest is the same as specific embodiments 4 to 6.

[0047] Specific embodiment eight: This embodiment differs from specific embodiments four to seven in that the degree of polymerization of the furfuryl alcohol oligomer in step two is 365 to 959. It is the same as specific embodiments four to seven.

[0048] Specific embodiment 9: This embodiment is different from specific embodiments 4 to 8 in that the vacuum and pressurization treatment described in step 4 is to first evacuate to a vacuum degree of -0.06MPa to -0.08MPa, then introduce air to a pressure of 0.6MPa to 0.8MPa, and treat for 3h to 5h under the pressure of 0.6MPa to 0.8MPa. The rest is the same as specific embodiments 4 to 8.

[0049] Specific embodiment 10: This embodiment differs from Specific embodiments 4 to 9 in that the heating and curing in step 5 is performed at a temperature of 95° C. to 105° C. for 3 to 5 hours. The rest is the same as Specific embodiments 4 to 9.

[0050] The following examples are used to verify the beneficial effects of the present invention:

[0051] Embodiment 1:

[0052] A method for preparing furfuryl alcohol / acrylamide composite modified wood is carried out according to the following steps:

[0053] 1. Weigh 30 parts of furfuryl alcohol, 2 parts of maleic anhydride, 4 parts of borax, 5.44 parts of acrylamide and 58.56 parts of solvent by mass;

[0054] The solvent is water;

[0055] 2. adding the weighed furfuryl alcohol, maleic anhydride and borax into a solvent to form an acidic solution, and then carrying out oligomerization reaction at a temperature of 60° C. for 1 hour to obtain furfuryl alcohol oligomers;

[0056] The degree of polymerization of the furfuryl alcohol oligomer is 959;

[0057] 3. Evenly mixing the furfuryl alcohol oligomer and the weighed acrylamide to obtain a furfuryl alcohol / acrylamide modifier;

[0058] Fourth, the wood is immersed in the furfuryl alcohol / acrylamide modifier, first evacuated to a vacuum degree of -0.08MPa, then introduced with air to a pressure of 0.8MPa, and treated at a pressure of 0.8MPa for 180min to obtain the impregnated wood;

[0059] The wood is poplar;

[0060] 5. The impregnated wood was heated and cured at 95°C for 3 hours, and finally dried to obtain furfuryl alcohol / acrylamide composite modified wood, which was recorded as FA-AM.

[0061] Comparative experiment: The difference between this comparative experiment and Example 1 is that: in step 1, 30 parts of furfuryl alcohol, 2 parts of maleic anhydride, 4 parts of borax and 64 parts of solvent are weighed by mass; step 3 is omitted; and in step 5, furfuryl alcohol-modified wood is obtained, which is recorded as FA. The rest is the same as Example 1.

[0062] Tested according to GB / T 1934.2-2009 standard: Figure 2 The figure is a comparison chart of the anti-expansion coefficient of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 and the furfuryl alcohol modified wood prepared in the comparative experiment. As can be seen from the figure, the anti-expansion coefficient of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 reaches 36.28%, which is about 8% higher than the anti-expansion coefficient of the furfuryl alcohol modified wood.

[0063] Tested according to GB / T 1927.5-2021 standard: Figure 3 The density comparison chart of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 and the furfuryl alcohol modified wood prepared in the comparative experiment. As can be seen from the figure, the density of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 reaches 0.55g / cm 3 , reaching the level of medium and high density wood species.

[0064] Tested according to DIN 52189-1-1981: Figure 4 This is a comparison chart of the impact strength of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 and the furfuryl alcohol modified wood prepared in the comparative experiment. As can be seen from the figure, the impact strength of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 reaches 28.64 kJ / m 2 The impact strength of the material is 44.43% higher than that of the furfuryl alcohol modified material.

[0065] Tested according to DIN 52186-1978: Figure 5 This is a comparison chart of the bending strength of the furfuryl alcohol / acrylamide composite-modified wood prepared in Example 1 and the furfuryl alcohol-modified wood prepared in the comparative experiment. Figure 6The figure is a comparison of the bending modulus of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 and the furfuryl alcohol modified wood prepared in the comparative experiment. As can be seen from the figure, the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 has a bending strength of 83.54MPa and a bending modulus of 14.83GPa, while compared with the bending strength (73.89MPa) and bending modulus (13.62GPa) of the furfuryl alcohol modified wood, the addition of acrylamide has no negative impact on the furfuryl alcohol modified wood, and also improves the performance.

[0066] Figure 7 The following are scanning electron microscope images, a) is untreated wood, and b) is the wood modified by furfuryl alcohol / acrylamide composite prepared in Example 1. As can be seen from the figure, furfuryl alcohol resin and acrylamide are mainly filled in the wood cell wall, causing the wood cell wall to be significantly thickened.

[0067] Tested according to GB / T 1927.5-2021 standard: Figure 8 The figure is a comparison chart of the weight gain rate of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 and the furfuryl alcohol modified wood prepared in the comparative experiment. As can be seen from the figure, the weight gain rate of the furfuryl alcohol / acrylamide composite modified wood prepared in Example 1 reaches 32.11%, which is about 10% higher than that of the furfuryl alcohol modified material.

Claims

1. A furfuryl alcohol / acrylamide composite modified wood, characterized in that It is obtained by modifying wood with furfuryl alcohol / acrylamide modifier; The furfuryl alcohol / acrylamide modifier is prepared from furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent.

2. The furfuryl alcohol / acrylamide composite modified wood according to claim 1, characterized in that The furfuryl alcohol / acrylamide modifier is prepared from 10 to 60 parts of furfuryl alcohol, 1 to 2 parts of maleic anhydride, 2 to 4 parts of borax, 1.81 to 10.86 parts of acrylamide and 23.14 to 85.19 parts of solvent in parts by mass.

3. The furfuryl alcohol / acrylamide composite modified wood according to claim 1, characterized in that The solvent is water or alcohol.

4. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 1, characterized in that It is carried out in the following steps:

1. Weigh furfuryl alcohol, maleic anhydride, borax, acrylamide and solvent; 2. adding the weighed furfuryl alcohol, maleic anhydride and borax into a solvent to form an acidic solution, and then carrying out an oligomerization reaction under heating conditions to obtain furfuryl alcohol oligomers; 3. Evenly mixing the furfuryl alcohol oligomer and the weighed acrylamide to obtain a furfuryl alcohol / acrylamide modifier; Fourth, the wood is impregnated in the furfuryl alcohol / acrylamide modifier, and then vacuum and pressure treated to obtain the impregnated wood; Fifth, the impregnated wood is heated and cured, and finally dried to obtain furfuryl alcohol / acrylamide composite-modified wood.

5. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that In step 1, 10 to 60 parts of furfuryl alcohol, 1 to 2 parts of maleic anhydride, 2 to 4 parts of borax, 1.81 to 10.86 parts of acrylamide and 23.14 to 85.19 parts of solvent are weighed by mass.

6. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that The solvent described in step 1 is water or alcohol.

7. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that In step 2, the oligomerization reaction is carried out at a temperature of 30° C. to 60° C. for 0.5 h to 1 h.

8. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that The degree of polymerization of the furfuryl alcohol oligomer described in step 2 is 365-959.

9. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that The vacuum and pressurization treatment described in step 4 specifically involves first evacuating to a vacuum degree of -0.06MPa to -0.08MPa, then introducing air to a pressure of 0.6MPa to 0.8MPa, and treating for 3h to 5h under a pressure of 0.6MPa to 0.8MPa.

10. The method for preparing furfuryl alcohol / acrylamide composite modified wood according to claim 4, characterized in that The heating and curing described in step 5 is specifically heating and curing at a temperature of 95° C. to 105° C. for 3 h to 5 h.

Citation Information

Cited By

  • Preparation method of novel polyethyleneimine grafted high-toughness furfuryl alcohol modified wood

    CN120363301A